A More Useful Agenda for Water Management. Issue 1 (1st September 2014) - Muller, Mike
Abstract : In this opinion editorial, New Water Policy and Practice International Advisory Board member Prof Mike Muller (Wits University Graduate School of Governance and former Director General of the Department of Water Affairs and Forestry, South Africa) begins with his thoughts on a more useful agenda for water management. Reflecting on examples of rights to water, privatisation and commoditisation of water in South Africa, the debate about dams and development in Africa, and river basins, regional institutions and state sovereignty, Mike presents the case that the current water management discourse has been distorted by strong interests with, on occasion, very significant negative impacts.